Pengembangan Sistem Informasi Pengawasan Proyek pada PT Blitz Energi Internusa - Trisna Yuli Heryanto; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Blitz Energi Internusa Inc is a company engaged in construction work, which has a vision to become a leading company and partner of choice for comprehensive construction solutions at a global level. To achieve this vision, good implementation is needed in monitoring the progress of a project. However, in its implementation there are several problems such as frequent errors in determining project progress data, as well as incomplete photo documentation and descriptions of project work activities. Based on this, an information system is needed that can help make it easier to supervise projects. Therefore, in working on this thesis, a project supervision information system was developed which is expected to be utilized by the project manager and superintendent as a means to implement better project supervision. This system is web-based and made with a waterfall approach, and utilizes the CodeIgniter framework based on the PHP programming language to facilitate access and further development of information systems at Blitz Energi Internusa Inc. The results of the validation testing show that from 11 test cases, all functions can run well and are declared valid. The results of the compatibility testing show that there are several problems for the Internet Explorer browser including not supporting some features in CSS. And the results of user acceptance testing obtained an acceptance percentage of 84% for superintendent actors, 88% for project manager actors and 80% for admin actors.